2014
DOI: 10.1007/s00068-014-0400-0
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic hemostatic fibrinogen assays detect fibrinolysis early

Abstract: Purpose Viscoelastic hemostatic assays are emerging as the standard-of-care in the early detection of post-injury coagulopathy. TEG and ROTEM are most commonly used. Although similar in technique, each uses different reagents, which may affect their sensitivity to detect fibrinolysis. Therefore, the purpose of this study is to determine the ability of each device to detect fibrinolysis. Methods TEG (Rapid, Kaolin, Functional Fibrinogen) and ROTEM (EXTEM, INTEM, FIBTEM) were run simultaneously on normal blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 26 publications
0
19
0
3
Order By: Relevance
“…Several studies have usedthe FIBTEM test in trauma patients 3,24,25 . Schöchl et al reported that FIBTEM MCF and FIBTEM A10 had a high predictive value for MT in trauma patients 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have usedthe FIBTEM test in trauma patients 3,24,25 . Schöchl et al reported that FIBTEM MCF and FIBTEM A10 had a high predictive value for MT in trauma patients 3 .…”
Section: Discussionmentioning
confidence: 99%
“…20 Additionally, impaired platelet function has been correlated to increased sensitivity to tPA. 21 Furthermore, there is evidence that FIBTEM, and its thromboelastography (TEG) correlate, namely, functional fibrinogen, detect clot lysis sooner than the EXTEM test 22 and increased sensitivity to hyperfibrinolysis has been shown in the FIBTEM versus EXTEM test in patients undergoing liver transplant. 23 Therefore, in the current study, it is plausible that the resistance to fibrinolysis observed was in part mediated by platelet function, and that cytochalasin-D–mediated platelet inhibition in the FIBTEM assay revealed differences in fibrinolytic activity among injury groups.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ichikawa et al demonstrated that an anti-Xa activity below 0.2 U/ml corresponding to a CT IN /CT HEP -ratio below 1.25 was not associated with increased postoperative mediastinal blood loss. In contrast, protamine overdose is not only associated with an elusively prolonged ACT (inhibition of factor V activation), [105,[142][143][144][145][146]153,157,195]: Prophylactic administration of TXA can be given within 3 h after trauma or delivery [142][143][144]195]. Continuous infusion of TXA can be performed in trauma [142][143][144].…”
Section: Korean J Anesthesiolmentioning
confidence: 99%